INDEPENDENCE OF PERSONALITY AS A PHENOMENON AND CONCEPT IN PSYCHOLOGICAL AND PEDAGOGICAL LITERATURE - S. Bobryshov; O. Schukina (Вестник Северо-Кавказского федерального университета)
The article is devoted to the problem of formation of independence among College students as a priority quality of personality, which allows to achieve the goal of modern education. It is shown that in conceptual terms, independence can be considered in three main directions: as a kind of independence; in inseparable connection with the ability of a person to plan his activities, with his self-activity and self-government; as a certain quality of personality, which is manifested in a sense of personal responsibility for their social and professional activities and behavior. The article also substantiates that independence is one of the key qualities of a person that can predict the position of a person, as well as allowing to move in the direction ofpersonal growth and creativity, which ultimately leads to the realization of the desire for self-improvement.